21st Century World Expositions facing territorial fragility - Cimadomo, Guido; Lecardane, Renzo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Expositions are not autonomous or homogeneous events, on the contrary, their development constitutes the plot of a discontinuous history, the mirror of a society in evolution that experiences its rules and its paradigms, showing them to the society. Through cartography and specific bibliography, in addition to the personal experiences of the authors, the events of Hannover (2000) that marks the beginning of the exhibitions of this century, Shanghai (2010), and Milan (2015) are analyzed. The aim is to understand the role and effects that exhibition events have on the transformation of the city and the territory, at a time when a renewed concern about the future of cities exists, subject to great tensions and demands. The land destined to these events is a link to join preexisting scattered urban fragments or to create new centralities, always with the result of increasing the metropolitan area thanks to the huge investments that exhibitions catalyze. The policies and strategies employed so far including sustainability and resilience, have varied in recent decades, but the results do not seem to provide evidence that any major event has been able to satisfactorily resolve the problems of fragility originated by urban pressures on the border between nature and built space, nor the permanent–temporal dichotomy that reach a key relevance in the planning of events.
Keywords: Urban fragility; Expositions; Urban transformations; Hannover; Shanghai; Milan